Inclusão digital na educação infantil: culturas infantis nas culturas contemporâneas - Penteado, Fabiana Rampelotto (2016)
Technological advances in recent years has caused a deep social unrest related to the inclusion of digital culture. In this sense, the school as a social promoter of human development, can‟t deny its legitimacy in the integration of digital culture to pedagogical practice in order to provide contemporary education of quality able to socialize and humanize the subject to favor the full development of educating (LDB 9.394/96). Connected to Graduate Program in Education of the Federal University of Santa Maria (UFSM), linked to the Line of Research School Practice and Public Policy (LP2) and the Group for Research and Contemporary Studies in Education and Childhood (GIECEI), the present study seeks subsidies for development of the Master of Research "Digital Inclusion in Childhood Education: Children‟s cultures in contemporary cultures". Presents the central theme of analysis education for children in contemporary sociocultural approach with an emphasis on digital inclusion, aiming to understand how children of preschool interact with contemporary digital culture in childhood education. Of exploratory nature, this research, is configured as a case study, instrumentalized through semi-structured interviews, and observations and interventions whith a group of children in preschool age enrolled in the Municipal Center Formiguinha Childhood Education, located in the municipality Formigueiro/RS. Grounded theory in political and philosophical studies of Arendt (2005; 2009), in Brazilian educational legislation and public policies for digital inclusion, as well as in the propositions about education and technology (BRITO, 2008; KENSKI, 2007; PAPERT, 1993 and TARJA, 2001), and Chauí (2006), Candau (2002), Cohn (2005), Kramer (2007), Barbosa (2000; 2007; 2014) and Corsaro (2011), sought to reconstruct the concept of children's culture. Finally, observe and intervene with the group of children led to understand that they themselves, from the interpretative reproduction of culture that elaborate, considering the characteristics of childhood, challenge yourself in the interaction with technological equipment, rebuilding thus their own perceptions about culture children and contemporary culture.